Marco Polo - Noonan, Jon. (New York : Crestwood House ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1993)
Describes the life and journeys of the Italian trader who became famous for his travels in Asia.
Includes index.
Keywords: Polo, Marco, -- 1254-1323? -- Travel -- Juvenile literature; Polo, Marco, -- 1254-1323?; Voyages and travels -- Juvenile literature; Explorers -- Italy -- Biography -- Juvenile literature; Explorers; Voyages and travels; China -- Description and travel -- Juvenile literature